2021
DOI: 10.3390/children8030184
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Dysfunctional Movements and Asymmetries in Young Normal Weight, Overweight, and Obese Children

Abstract: This study evaluated overall performance on the functional movement screen (FMS), prevalence of asymmetries and dysfunctional movements, and the relationship between measures of adiposity and the FMS score. Methods: Ninety-four (53 boys; 41 girls) 10–12-year-old children in Hungary and Germany who were participating in daily physical education performed the FMS. The mean FMS score in girls (14.1) was significantly higher than in boys (12.9). Individual test item scores were similar, except girls scored higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
“…Other studies have reported no significant differences in the FMS scores between boys and girls [ 36 , 38 , 41 , 44 , 48 , 49 , 58 , 62 , 63 , 76 , 81 , 83 , 86 , 87 , 89 , 90 , 91 , 93 , 99 , 103 , 110 ]. Fewer studies have reported that girls perform better than boys [ 32 , 40 , 45 , 54 , 55 , 59 , 88 , 108 ] and even fewer studies report that boys perform better than girls [ 107 , 111 ].…”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 3 more Smart Citations